2020
DOI: 10.1007/s00421-020-04458-7
|View full text |Cite
|
Sign up to set email alerts
|

Head-down tilt bed rest with or without artificial gravity is not associated with motor unit remodeling

Abstract: Purpose The objective of this study was to assess whether artificial gravity attenuates any long-duration head-down 60 bed rest (HDBR)-induced alterations in motor unit (MU) properties. Methods Twenty-four healthy participants (16 men; 8 women; 26–54 years) underwent 60-day HDBR with (n = 16) or without (n = 8) 30 min artificial gravity daily induced by whole-body centrifugation. Compound muscle action potential (CMAP), MU number (MUNIX) and MU size (MUSIX) were estimated using the method of Motor Unit Numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…The absence of changes in serum markers of muscle wasting, neurotrophic factors and C-terminal agrin fragment corresponds with the absence of changes in the number (MUNIX) and size (MUSIX) of motor units found in the same bed-rest study [61] and normal muscle activation during a fatigue test after 21 days bed rest [13]. In combination, these observations suggest that the neuromuscular interaction is not compromised during bed rest of up to 60 days.…”
Section: C-terminal Agrin Fragmentmentioning
confidence: 57%
“…The absence of changes in serum markers of muscle wasting, neurotrophic factors and C-terminal agrin fragment corresponds with the absence of changes in the number (MUNIX) and size (MUSIX) of motor units found in the same bed-rest study [61] and normal muscle activation during a fatigue test after 21 days bed rest [13]. In combination, these observations suggest that the neuromuscular interaction is not compromised during bed rest of up to 60 days.…”
Section: C-terminal Agrin Fragmentmentioning
confidence: 57%
“…63% MVC contractions ( Oliva-Lozano and Muyor, 2020 ) Thus, whilst the muscle recruitment in our exercises appears to be moderate, the failure to observe functionally significant different with those performed upright suggests that more complicated, and or aggressive trunk muscle exercises should be evaluated acutely during SAHC. Should they prove to be feasible, tolerable and induce trunk muscle activation likely to be ergogenic then a AG-training study employing such during long duration head down tilt may be warranted to see if they plug a key operational countermeasure gap ( Green and Scott, 2017 ) given that daily passive AG at 1 g at CoM is well tolerated during head down tilt bed rest ( Frett et al, 2020a ) but provides a relatively low physiological load ( Kramer et al, 2020a ), and appears insufficient to ameliorate multi-system bed rest-induced deconditioning ( Attias et al, 2020 ; Martino et al, 2020 ; Hoffmann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that daily passive centrifugation at 1 g at the participants Center of Mass (CoM) is well tolerated during a 60-days bed rest period ( Frett et al, 2020a ). Nevertheless, 30 min of daily passive centrifugation with 1 g at the CoM provides a relatively low physiological load ( Kramer et al, 2020a ), and recent data suggests that it is insufficient to ameliorate bed rest-induced multi-organ deconditioning ( Attias et al, 2020 ; Hoffmann et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cardiovascular adaptation to HDTBR was not affected by daily artificial gravity training. Other analyses from AGBRESA also report no relevant influences of the artificial gravity intervention on physiological outcomes (Attias et al, 2020;Hoffmann et al, 2020;Kramer et al, 2020;Ganse et al, 2021;Lecheler et al, 2021). Combining artificial gravity with exercise holds promise for future bed rest studies (Diaz-Artiles et al, 2018).…”
Section: Discussionmentioning
confidence: 99%